Pelatihan Pemanfaatan Media Sosial Untuk Mengenalkan Wisata Air Terjun Desa Belitar Seberang, Kecamatan Sindang Kelingi,Kabupaten Rejang Lebong - wagini wagini; Suwarni Suwarni; Tito Irwanto; Dewi Harweni; Zelinda Prasentia (Universitas Dehasen Bengkulu, 2023)
Belitar Seberang Village is one of the villages that has a tourist object that has been recognized by the wider community, where Belitar Seberang Village has a very nice and unspoiled Waterfall. There are many waterfalls owned by Belitar Seberang Village and the most famous are Tri Sakti Waterfall and Puspa Dewi Waterfall. The use of social media for the development and promotion of tourism destinations is being carried out by the people of Indonesia, both from the government and the private sector. Belitar Seberang Village is no exception, which uses social media to introduce Waterfall tourism to the wider community, both local, national and foreign.This service focuses on the application of social media as an effort to introduce the Belitar Seberang Village waterfall tour. The goal is to find out how people use social media to market waterfall tourism in Belitar Seberang Village. There are quite a lot of tourism potentials in Belitar Seberang Village. the use of social media empirically can improve the welfare of the people of Belitar Seberang Village. And social media really helps the community and village officials to get to know more about and improve the quality and quantity in introducing tourism in Belitar Seberang Village, Sidang Kelingi District, Rejang Lebong Regency.